Influence of dietary taurine and housing density on oviduct function in laying hens - Dai, Bin (Zhejiang University Press, 2015)

(untitled) (J Zhejiang Univ Sci B)
Experiments were conducted to study the effects of dietary taurine and housing density on oviduct function in laying hens. Green-shell laying hens were randomly assigned to a free range group and two caged groups, one with low-density and the other with high-density housing. Each group was further divided into control (C) and taurine treatment (T) groups. All hens were fed the same basic diet except that the T groups’ diet was supplemented with 0.1% taurine. The experiment lasted 15 d. Survival rates, laying rates, daily feed consumption, and daily weight gain were recorded. Histological changes, inflammatory mediator levels, and oxidation and anti-oxidation levels were determined. The results show that dietary taurine supplementation and reduced housing density significantly attenuated pathophysiological changes in the oviduct. Nuclear factor-κB (NF-κB) DNA binding activity increased significantly in the high-density housing group compared with the two other housing groups and was reduced by taurine supplementation. Tumor necrosis factor-α (TNF-α) mRNA expression in the high-density and low-density C and T groups increased significantly. In the free range and low-density groups, dietary taurine significantly reduced the expression of TNF-α mRNA. Supplementation with taurine decreased interferon-γ (IFN-γ) mRNA expression significantly in the low-density groups. Interleukin 4 (IL-4) mRNA expression was significantly higher in caged hens. IL-10 mRNA expression was higher in the high-density C group than in the free range and low-density C groups. Supplementation with taurine decreased IL-10 mRNA expression significantly in the high-density group and increased superoxide dismutase (SOD) activity in the free range hens. We conclude that taurine has important protective effects against oviduct damage. Reducing housing density also results in less oxidative stress, less inflammatory cell infiltration, and lower levels of inflammatory mediators in the oviduct. Therefore, both dietary taurine and reduced housing density can ameliorate oviduct injury, enhance oviduct health, and promote egg production in laying hens.